2005
DOI: 10.1158/1078-0432.ccr-05-1410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Cancer Vaccines Targeting Tyrosinase: Plasmid DNA and Recombinant Alphavirus Replicon Particles

Abstract: Purpose: Immunization of mice with xenogeneic DNA encoding human tyrosinase-related proteins1and 2 breaks tolerance to these self-antigens and leads to tumor rejection.Viral vectors used alone or in heterologous DNA prime/viral boost combinations have shown improved responses to certain infectious diseases. The purpose of this study was to compare viral and plasmid DNA in combination vaccination strategies in the context of a tumor antigen. Experimental Design: Using tyrosinase as a prototypical differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
4
38
0
1
Order By: Relevance
“…Some natural autoantibodies may have antitumor effects: tyrosinase, involved in the synthesis of melanin, is a melanoma-associated antigen (30), and carbonic anhydrase IX is a tumor-associated antigen in renal cell carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some natural autoantibodies may have antitumor effects: tyrosinase, involved in the synthesis of melanin, is a melanoma-associated antigen (30), and carbonic anhydrase IX is a tumor-associated antigen in renal cell carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…We generated a replicon expression plasmid containing the CEA gene with the Cap-1(6D) mutation (15) called CEA(6D) VRP (AVX701) (Supplemental Figure 5) as previously described (9,13,27). It was formulated so that the maximum feasible dose to administer in the clinical trial was 4 × 10 8 IU.…”
Section: Methodsmentioning
confidence: 99%
“…Other advantages of VRP are their tropism for, and maturation of (5), DCs, which could result in enhanced T cell activation. A number of preclinical studies have reported that VRP induce potent immunity despite the presence of neutralizing antibodies (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Using tyrosinase as a prototypical melanocyte differentiation antigen, we recently showed that Venezuelan equine encephalitis virus -based VRP induced robust B-cell and T-cell responses and improved survival in mice challenged with B16 melanoma cells. In this setting, more potent and protective responses were elicited using a syngeneic (murine) rather than a xenogeneic (human) form of tyrosinase (17). Based on these findings, we prepared VRP encoding human PSMA for preclinical evaluation as a potential vaccine therapy for prostate cancer in man.…”
mentioning
confidence: 99%